Imagine! Motor Imagery as an Adjunct to Conventional Neuro Rehabilitation after Stroke - Ayesha Ahmad, (Pakistan Journal of Medical & Health Sciences, 2024)
Stroke occurs due to obstructed blood flow in the brain that eventually leads to cell death. More than 13.7 million episodes of stroke occur each year in the world. The three main types of stroke are Transient Ischemic Attack (TIA), ischemic stroke, and hemorrhagic stroke. In TIA the interruption is temporary and there are no permanent neurological deficits. Ischemic stroke is the commonest (about 87%) and occurs due to obstructed blood supply of the brain. Hemorrhagic stroke is caused by ruptured blood vessel. Stroke is broadly divided into total anterior circulation stroke (TACS), partial anterior circulation stroke (PACS), lacunar stroke (LACS) and posterior circulation stroke (POCS) with symptoms including hemiparesis, sensory changes, visuospatial problems, cognitive impairments etc. The deficits depend upon the area of brain affected. Motor impairment effects about 80% of patients1. Recovery from stroke requires physical therapy or rehabilitation2.